Isle of devils, isle of saints : an Atlantic history of Bermuda, 1609-1684 - Jarvis, Michael (Michael J.) (Early America., 2022)
Revealing the dynamic interplay of race, gender, slavery, and environment at the dawn of English America, Jarvis's work challenges us to rethink how Europeans and Africans became distinctly American within the crucible of colonization.